The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Current Directions in Autoimmunity 2008
DOI: 10.1159/000131410
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis

Abstract: Allergic contact dermatitis is a classic example of a cell mediated hypersensitivity reaction in the skin. This occurs as a result of xenobiotic chemicals penetrating into the skin, chemically reacting with self proteins, eventually resulting in a hapten-specific immune response. It is precisely because of this localized immune response that allergic signs and symptoms occur (redness, edema, warmth and pruritus). It has been known for years that conventional T-cells (CD4+ or CD8+ T-cells that express a T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 92 publications
(121 reference statements)
1
60
0
2
Order By: Relevance
“…Allergic contact dermatitis (ACD) caused by metallic ions and other reactive haptens is a T cell-mediated inflammatory skin disease (4)(5)(6). ACD is characterized by two phases: a sensitization phase and an elicitation phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic contact dermatitis (ACD) caused by metallic ions and other reactive haptens is a T cell-mediated inflammatory skin disease (4)(5)(6). ACD is characterized by two phases: a sensitization phase and an elicitation phase.…”
mentioning
confidence: 99%
“…IL-12 is primarily produced by macrophages and DCs mainly in response to danger signals such as TLR agonists and plays a major role in IFN-g production by immune cells, driving a Th1/Tc1-type response (13)(14)(15)(16). Many authors have demonstrated that CD8 + cytotoxic T lymphocytes are the main effector cells of ACD and observed their early recruitment in the skin postchallenge with chemical sensitizers (6,17). Injection of IL-12 during the sensitization phase favors CD8 + T cell differentiation and increases the ACD reaction (18).…”
mentioning
confidence: 99%
“…Under normal conditions, keratinocytes express low levels of the costimulatory molecules CD80 and CD86. 19 These molecules bind to their receptors in T cells (CD28/CTLA-4 -cytotoxic TL-associated antigen-4) and are necessary for leading to a second effective signal. 19 In the absence of a second signal, the TL become anergic.…”
Section: Keratinocytesmentioning
confidence: 99%
“…19 These molecules bind to their receptors in T cells (CD28/CTLA-4 -cytotoxic TL-associated antigen-4) and are necessary for leading to a second effective signal. 19 In the absence of a second signal, the TL become anergic. 127.128 These anergic TL express a large amount of IL-2 receptors and therefore compete with effector and memory T cells for this growth factor.…”
Section: Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation